A back contact battery with improved contact characteristics and its preparation method and application
By setting alternately arranged semiconductor regions on the back of the silicon wafer of the back contact battery, opening isolation grooves on the transparent conductive film layer, and doping metal materials on the surface of its surface, the problem of poor contact characteristics in existing back contact batteries is solved, and lower resistivity and higher battery efficiency are achieved.
Patent Information
- Application Number
- CN202510026036.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The contact characteristics between the transparent conductive film layer, the semiconductor film layer, and the metal electrode in the existing back contact battery are poor, which affects the battery efficiency.
The semiconductor distribution layers of the N-type semiconductor region and the P-type semiconductor region alternately arranged on the back of the silicon wafer, and a transparent conductive film layer is provided on the outer surface thereof, and an isolation groove is opened. The N-type metal electrode and the P-type metal electrode are arranged on the outer surface of the respective transparent conductive film layers of the N-type semiconductor region and the P-type semiconductor region. The surface doped metal material of the transparent conductive film layer forms a doping region, and the doping depth and oxygen doping amount are controlled to optimize contact characteristics.
The contact characteristics between the transparent conductive film layer and the semiconductor layer and the metal electrode are improved, the resistivity of the transparent conductive film layer is reduced, and the battery efficiency is improved.
Smart Images

Figure CN119451306B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of back contact batteries, and in particular relates to a back contact battery with improved contact characteristics, a preparation method and an application thereof. Background Art
[0002] At present, back-contact batteries generally include a battery substrate with N-type semiconductor regions and P-type semiconductor regions arranged alternately on the back, a transparent conductive film layer arranged on the outer surface of the battery substrate, and a metal electrode (generally low-temperature silver paste printing or electroplated copper grid) arranged on the outer surface of the transparent conductive film layer.
[0003] In the above-mentioned existing structure, the metal electrode and the semiconductor of different polarity are connected by a transparent conductive film layer. Since the back of the back contact battery has both N-type semiconductor and P-type semiconductor, the transparent conductive film layer is generally n-type, and it is easy to form an ohmic contact between the N-type transparent conductive film layer and the N-type semiconductor. Therefore, the contact resistance between the transparent conductive film layer and the N-type semiconductor region is small. In order for the N-type transparent conductive film layer and the P-type semiconductor to form an ohmic contact, it is necessary to adjust the coating process to improve the work function of the transparent conductive film layer. Because the N-type semiconductor and the P-type semiconductor are on both sides of the battery, HJT is realized by using different ITO coating processes (or material ratios) on the front and back sides. However, it is difficult to match the transparent conductive film layer with different semiconductor layers by adjusting the film parameters (such as work function, carrier concentration and other parameters) once deposited, and it is difficult to achieve the best film characteristics, which limits the continued improvement of battery efficiency to a certain extent. In this regard, it is difficult for the transparent conductive film layer to contact and match with different semiconductor layers by adjusting the parameters. In addition, the metal electrode made at low temperature relies on the contact between the metal and the semiconductor film layer for conductivity, and it is difficult to achieve high-temperature silver paste sintering to achieve good contact characteristics, thereby affecting the battery efficiency.
[0004] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defect of the prior art that the contact characteristics between the transparent conductive film layer and the semiconductor film layer and the metal electrode in the back-contact battery are poor, which affects the battery efficiency, and to provide a back-contact battery with improved contact characteristics and a preparation method and application thereof, which can well match semiconductors of different polarities on the back, improve the contact characteristics between the metal electrode and the transparent conductive film layer, and between the transparent conductive film layer and the semiconductor layer, enhance the conductivity of the transparent conductive film layer, reduce the resistivity of the transparent conductive film layer, and reflect the effect of reducing the overall resistance from a macroscopic measurement, thereby improving the battery efficiency.
[0006] In order to achieve the above-mentioned purpose, in a first aspect, the present invention provides a back-contact battery with improved contact characteristics, comprising a silicon wafer, a semiconductor distribution layer comprising alternately arranged N-type semiconductor regions and P-type semiconductor regions arranged on the back of the silicon wafer, a transparent conductive film layer arranged on the outer surface of the semiconductor distribution layer, an isolation groove is provided on the transparent conductive film layer corresponding to the boundary region between the N-type semiconductor region and the adjacent P-type semiconductor region, and an N-type region metal electrode and a P-type region metal electrode are provided on the outer surface of the corresponding transparent conductive film layer of the N-type semiconductor region and the P-type semiconductor region, the N-type semiconductor region and the P-type semiconductor region both comprising a silicon layer, the surface layer of the transparent conductive film layer is at least partially doped with a metal material to form a doped region, and the average doping concentration of the metal material in the doped region is 1e18cm -3 -5e22cm -3 The proportion of oxygen vacancies in the transparent conductive film layer to the total oxygen atoms contained is 5%-60%, and doping regions are respectively set on the transparent conductive film layers that the N-type region metal electrode and the P-type region metal electrode contact respectively.
[0007] Among them, when the metal material is a metal of an acceptor impurity in the silicon layer, the doping depth D1 of the doping region corresponding to the N-type semiconductor region is 20%-90% of the thickness of the transparent conductive film layer, and the doping depth D2 of the doping region corresponding to the P-type semiconductor region is 30%-100% of the thickness of the transparent conductive film layer; and D1 is less than D2.
[0008] When the metal material is a metal as a donor impurity in the silicon layer, the doping depth D1 of the doping region corresponding to the N-type semiconductor region is 30%-100% of the thickness of the transparent conductive film layer, and the doping depth D2 of the doping region corresponding to the P-type semiconductor region is 20%-90% of the thickness of the transparent conductive film layer; and D1 is greater than D2.
[0009] Preferably, when the metal material is a metal of an acceptor impurity in the silicon layer, the ratio of D1 to D2 is 1:1.25-6; when the metal material is a metal of a donor impurity in the silicon layer, the ratio of D1 to D2 is 1:0.3-0.8.
[0010] In some preferred embodiments of the present invention, the metal material in the doping region is distributed in at least one of the forms of dots, lines, and meshes, and / or the doped metal material is a nano-metal material.
[0011] In some preferred embodiments of the present invention, the metal material is selected from at least one of silver, zinc and tin.
[0012] Preferably, the metal as an acceptor impurity includes at least one of silver and zinc, and the metal as a donor impurity includes tin.
[0013] In some preferred embodiments of the present invention, when the metal material is a metal of an acceptor impurity in the silicon layer, the ratio of the average value of the doping depth of the metal material in the partial doping region where the N-type region metal electrode and the P-type region metal electrode respectively contact is 1:1.1-3; when the metal material is a metal of a donor impurity in the silicon layer, the ratio of the average value of the doping depth of the metal material in the partial doping region where the N-type region metal electrode and the P-type region metal electrode respectively contact is 1:0.5-0.9.
[0014] In some preferred embodiments of the present invention, on the plane where the back surface is located, the area of the doped region accounts for 5%-80% of the area of the transparent conductive film layer.
[0015] In some preferred embodiments of the present invention, the thickness of the transparent conductive film layer is 10-150 nm.
[0016] In some preferred embodiments of the present invention, the back contact cell with improved contact characteristics further comprises at least one of the following structures:
[0017] Structure 1: The semiconductor distribution layer also includes an overlapping region between the N-type semiconductor region and the P-type semiconductor region, the overlapping region is formed by extending the end of the P-type semiconductor of the P-type semiconductor region and overlapping the outer surface of the end of the adjacent N-type semiconductor region, and the isolation groove is opened on the transparent conductive film layer corresponding to the overlapping region; a mask layer is set between the overlapping P-type semiconductor and the N-type semiconductor in the overlapping region or no mask layer is set;
[0018] Structure 2: The back side of the silicon wafer corresponding to the N-type semiconductor region is a polished surface, and the back side of the silicon wafer corresponding to the P-type semiconductor region is a velvet surface;
[0019] Structure 3: The back contact cell with improved contact characteristics further comprises a front passivation layer and an anti-reflection layer arranged on the front side of the silicon wafer;
[0020] Structure 4: The material of the metal material is at least partially the same as the material of the corresponding metal electrode;
[0021] Structure 5: The metal material is selected from silver, and the N-type region metal electrode and the P-type region metal electrode are both silver paste electrodes.
[0022] In a second aspect, the present invention provides a method for preparing a back contact battery, comprising the following steps:
[0023] S1. Providing a battery substrate, the battery substrate comprising a silicon wafer and a semiconductor distribution layer deposited on the back of the silicon wafer and comprising alternatingly arranged N-type semiconductor regions and P-type semiconductor regions; both the N-type semiconductor regions and the P-type semiconductor regions comprise a silicon layer;
[0024] S2, depositing a transparent conductive film layer on the back of the battery substrate, controlling the oxygen content of the coating atmosphere corresponding to the transparent conductive film layer to be 0.1%-3% by volume; and opening an isolation groove on the transparent conductive film layer corresponding to the boundary area between the N-type semiconductor region and the adjacent P-type semiconductor region;
[0025] S3, coating a nano-metal material on at least part of the outer surface of the transparent conductive film layer, wherein the coating distribution density of the nano-metal material on the area of the transparent conductive film layer corresponding to the N-type semiconductor region and the P-type semiconductor region is different and the coating distribution density is 2%-80% based on the projected area; the diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region and the P-type semiconductor region is at least partially different;
[0026] S4. Perform microwave heating treatment on the nano-metal material on the back side under the protection of inert gas, so that at least part of the nano-metal material is doped into the transparent conductive film layer to form a doping region, and the doping depth of the doping region is controlled to be 20%-100% of the thickness of the transparent conductive film layer, and the average doping concentration of the metal material in the doping region is 1e18cm -3 -5e22cm -3 ;
[0027] S5. Forming an N-type region metal electrode and a P-type region metal electrode on the outer surfaces of the corresponding transparent conductive film layers in the N-type semiconductor region and the P-type semiconductor region, respectively.
[0028] In some preferred embodiments of the present invention, the nanometal material in S3 is introduced in the form of nanoparticles and / or nanowires, and / or the coated nanometal material is distributed in at least one of the forms of dots, lines, and meshes.
[0029] Preferably, the diameter of the nanometal material is 10-3000 nm.
[0030] Preferably, the median diameter of the nanometal material coated on the transparent conductive film layer area corresponding to the N-type semiconductor region is 10-3000nm, and the median diameter of the nanometal material coated on the transparent conductive film layer area corresponding to the P-type semiconductor region is 10-1500nm.
[0031] Preferably, when the metal material is a metal that is an acceptor impurity in the silicon layer, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region is 5-60 times the thickness of the transparent conductive film layer, and the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region is 1-40 times the thickness of the transparent conductive film layer.
[0032] Preferably, when the metal material is a metal as a donor impurity in the silicon layer, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region is 1-30 times the thickness of the transparent conductive film layer, and the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region is 5-80 times the thickness of the transparent conductive film layer.
[0033] Further preferably, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region is N1, and the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region is P1, and it satisfies: when the metal material is a metal of an acceptor impurity in the silicon layer, N1 is greater than P1; when the metal material is a metal of a donor impurity in the silicon layer, N1 is less than P1.
[0034] Further preferably, when the metal material is a metal of an acceptor impurity in the silicon layer, the ratio of N1 to P1 is 1:0.01-0.9; when the metal material is a metal of a donor impurity in the silicon layer, the ratio of N1 to P1 is 1:1.2-100.
[0035] In some preferred embodiments of the present invention, the coating area of the nano-metal material in S3 accounts for 5%-80% of the area of the transparent conductive film layer.
[0036] In some preferred embodiments of the present invention, the coating distribution density of the nanometal material in S3 on the transparent conductive film layer area corresponding to the preset N-type semiconductor region is 2%-30% by projected area, and the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset P-type semiconductor region is 15%-80% by projected area.
[0037] In some preferred embodiments of the present invention, when the metal material is a metal of an acceptor impurity in the silicon layer, the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset N-type semiconductor region is less than the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset P-type semiconductor region; when the metal material is a metal of a donor impurity in the silicon layer, the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset N-type semiconductor region is greater than the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset P-type semiconductor region.
[0038] In some preferred embodiments of the present invention, the microwave heating treatment in S4 lasts for 3-30 seconds.
[0039] In some preferred embodiments of the present invention, after the microwave heating treatment in S4, at least part of the nano-metal material is attached to the surface of the transparent conductive film layer in a hemispherical shape, and part of the hemispherical nano-metal material contacts the corresponding metal electrode material in S5.
[0040] In some preferred embodiments of the present invention, the coating method of the nano-metal material in S3 is any one of inkjet printing, dispensing, and pad printing.
[0041] In some preferred embodiments of the present invention, when the metal material is a metal of an acceptor impurity in the silicon layer, the doping depth of the doping region corresponding to the N-type semiconductor region is controlled to be 20%-90% of the thickness of the transparent conductive film layer, and the doping depth of the doping region corresponding to the P-type semiconductor region is controlled to be 30%-100% of the thickness of the transparent conductive film layer;
[0042] When the metal material is a metal as a donor impurity in the silicon layer, the doping depth of the doping region corresponding to the N-type semiconductor region is controlled to be 30%-100% of the thickness of the transparent conductive film layer, and the doping depth of the doping region corresponding to the P-type semiconductor region is controlled to be 20%-90% of the thickness of the transparent conductive film layer.
[0043] In a third aspect, the present invention provides a back-contact battery with improved contact characteristics, which is prepared by the method for preparing a back-contact battery described in the second aspect.
[0044] In a fourth aspect, the present invention provides a photovoltaic module, which includes the back-contact cell with improved contact characteristics described in the first aspect, or includes the back-contact cell with improved contact characteristics described in the third aspect.
[0045] Beneficial effects:
[0046] The present invention adopts the above technical scheme, especially sets doping regions with specific doping depths and doping amounts for the parts of the transparent conductive film layer corresponding to the N-type semiconductor region and the P-type semiconductor region of the back contact battery close to the metal electrodes of different polarities, cooperates with a suitable oxygen doping amount, controls oxygen vacancies, and increases the carrier concentration; and also cooperates with controlling the doping depths of the doping regions corresponding to the N-type region metal electrode and the P-type region metal electrode in different ranges, increases the free electrons in the film layer and increases the carrier concentration, thereby preventing the silver ions from diffusing to the polycrystalline or amorphous layer in the semiconductor region below the transparent conductive film layer, making the transparent conductive film layer and the N-type region metal electrode and the N-type semiconductor region respectively have excellent ohmic contacts, thereby increasing the carrier concentration, and at the same time, the transparent conductive film layer and the P-type region metal electrode and the P-type semiconductor region respectively have good contact characteristics, thereby reducing the overall resistance and improving the battery efficiency.
[0047] Moreover, the present invention also controls the oxygen doping amount of the transparent conductive film layer within a suitable range, which can increase the ratio of oxygen vacancies in the transparent conductive film layer to the total amount of oxygen atoms contained, thereby optimizing the contact characteristics with the N-type polycrystalline layer; and while adjusting the oxygen doping amount of the transparent conductive film layer, the doping depth of the nano-metal material in different conductive regions is controlled, thereby well matching the semiconductors of different polarities on the back side, reducing the contact characteristics between the metal electrode and the transparent conductive film layer, and between the transparent conductive film layer and the semiconductor layer, and at the same time, locally doping the transparent conductive film layer in an appropriate amount can enhance the conductivity of the transparent conductive film layer, reduce the resistivity of the transparent conductive film layer, and reflect the effect of reducing the overall resistance from a macroscopic measurement, thereby improving the battery efficiency. Under the same conditions, if the conventional method of adding a nano-metal material layer to assist in improving the conductivity of the transparent conductive film layer is adopted, the poor adhesion of the metal material or the introduced adhesion enhancing material will directly affect the contact between the metal material and the semiconductor film layer or slurry, and there will be no improvement on the battery contact characteristics, thereby affecting the battery efficiency; and the contact effect between the ordinary coated nano-metal material and the semiconductor material is not ideal. Since there are both N-type semiconductor regions and P-type semiconductor regions on the back of the back-contact battery, the conventional method of changing the thickness ratio or oxygen doping amount of the transparent conductive film layer will inevitably cause the N-type semiconductor region to be out of the optimal match, making it difficult to improve the battery contact characteristics, thereby affecting the battery efficiency.
[0048] Specifically, the present invention controls the doping depth of the transparent conductive film layer metal material corresponding to the N-type semiconductor region and the P-type semiconductor region in different ranges by utilizing the different characteristics of microwave thermal absorption efficiency of nano-metal particles of different diameters and different distribution densities. Taking nano-silver particles as an example, since silver ions provide holes for acceptor impurities in polycrystalline silicon and amorphous silicon, and provide electrons as donor impurities in transparent conductive film layers such as ITO. Therefore, it is necessary to control the doping depth of silver doped on the transparent conductive film layer in the N-type region to prevent the silver ions from diffusing into the N-type polycrystalline or amorphous layer. For the P-type amorphous layer, silver ions act as acceptor impurities, and appropriate doping can increase the hole density of the local amorphous layer and improve the conductivity. Therefore, the doping depth of silver ions in the transparent conductive film layer in the P-type region can be greater, reaching or approaching 100% of the thickness of the transparent conductive film layer, and improving the contact characteristics between the P-type amorphous and the transparent conductive film layer.
[0049] Since the silver ion doping depth is limited in the N-type region, the entire transparent conductive film layer cannot be doped to increase the carrier concentration and mobility, especially the carrier concentration and mobility of the transparent conductive film layer close to the N-type polycrystalline layer. It is necessary to optimize the transparent conductive film deposition process. Therefore, in order to improve the contact characteristics between the transparent conductive film layer and the N-type polycrystalline layer, the oxygen content of the transparent conductive film deposition process is controlled by adjusting the oxygen doping amount during the deposition of the transparent conductive film layer to increase the proportion of oxygen vacancies in the transparent conductive film layer to the total amount of oxygen atoms contained, thereby optimizing the contact characteristics with the N-type polycrystalline layer. Under the same conditions, excessive oxygen doping will lead to a decrease in oxygen vacancies, while insufficient oxygen doping will lead to an increase in defect density and affect the film properties.
[0050] The nano-metal particles attached to the surface of the transparent conductive film layer melt and only partially incorporate into the transparent conductive film layer. The surface attached part can establish a good connection with the metal electrode, thereby improving the contact effect between the metal electrode and the transparent conductive film layer.
[0051] In the preparation method of the present invention, nano-metal materials are coated on the surface of the transparent conductive film layer and subjected to microwave heating treatment. Compared with traditional heat treatment, it is easier to control the heating of the nano-metal materials in a very short time (depending on the microwave energy, the treatment can generally be completed within 3-30 seconds). At the same time, due to the different microwave absorption of semiconductors and metals, it is easier to achieve selective heating treatment of nano-metal materials, and the impact on the battery substrate is relatively small (for back-contact batteries, the control of the battery substrate temperature is particularly important). The nano-metal materials are heated and melted without damaging the battery substrate, and some ions enter the transparent conductive film layer for local appropriate doping, which can optimize the local doping of the transparent conductive film layer, reduce the contact characteristics between the metal electrode and the transparent conductive film layer, and between the transparent conductive film layer and the semiconductor layer, enhance the conductivity of the transparent conductive film layer, and reduce the resistivity of the transparent conductive film layer, thereby improving the battery efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0053] Figure 1 The schematic diagram of the structure of the metal electrode contact portion of a back contact battery according to one embodiment.
[0054] Figure 2is a SEM image of an outer surface of a corresponding area of an N-type semiconductor region after being coated with spherical and linear nano-metal materials but not subjected to microwave heat treatment in one embodiment;
[0055] Figure 3 The SEM image of an embodiment of the N-type semiconductor region corresponding to the region after the outer surface is coated with spherical nano-metal material and subjected to microwave heat treatment;
[0056] Figure 4 This is a SEM picture of another embodiment in which the outer surface of the corresponding area of the N-type semiconductor region is coated with spherical and linear nano-metal materials and subjected to microwave heat treatment.
[0057] Figure 5 is a SEM image of an outer surface of a corresponding area of a P-type semiconductor region after being coated with spherical and linear nano-metal materials but not subjected to microwave heat treatment in one embodiment;
[0058] Figure 6 The SEM image of the outer surface of the corresponding area of the P-type semiconductor region after being coated with spherical nano-metal material and subjected to microwave heat treatment in one embodiment;
[0059] Figure 7 This is a SEM picture of another embodiment in which the outer surface of the corresponding area of the P-type semiconductor region is coated with spherical and linear nano-metal materials and subjected to microwave heat treatment.
[0060] Description of Reference Numerals
[0061] 1. Silicon wafer, 21. N-type semiconductor region, 22. P-type semiconductor region, 31. First transparent conductive film layer, 32. Second transparent conductive film layer, 33. Isolation trench, 41. N-type region metal electrode, 42. P-type region metal electrode, 5. Nanometal material, 51. First doped region, 52. Second doped region. DETAILED DESCRIPTION
[0062] In the present invention, unless otherwise specified, directional words such as "upper, lower, left, right" are generally understood in conjunction with the directions shown in the drawings and actual applications.
[0063] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0064] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0065] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Among them, the terms "optional" and "optional" all mean that they may be included or not included (or may be present or not).
[0066] In the present invention, the area close to the silicon wafer is referred to as the inside, and the area far from the silicon wafer is referred to as the outside.
[0067] In the present invention, the ratio of oxygen vacancies to the total amount of oxygen atoms refers to the percentage of oxygen vacancies to the total amount of oxygen atoms contained in the transparent conductive film layer calculated by analyzing the spectrum obtained by X-ray photoelectron spectroscopy (XPS) analysis test and the integral area ratio of characteristic peaks of different defects.
[0068] In the present invention, the definition of acceptor impurities is: impurity atoms artificially added into the corresponding semiconductor material (such as silicon layer), which can accept electrons in the corresponding semiconductor material to generate conductive holes and form negative charge centers, which are called acceptor impurities.
[0069] The definition of donor impurities is: it refers to the impurity elements of a certain chemical element artificially added to the corresponding semiconductor material (such as silicon layer). The excess valence electrons produced by the difference between the impurity elements and the valence electrons of the semiconductor material will break free from their constraints and become conductive free electrons. After the impurities are ionized, positive charge centers are formed. These added elements are called donor impurities.
[0070] In a first aspect, the present invention provides a back-contact battery with improved contact characteristics, comprising a silicon wafer, a semiconductor distribution layer comprising alternately arranged N-type semiconductor regions and P-type semiconductor regions arranged on the back of the silicon wafer, a transparent conductive film layer arranged on the outer surface of the semiconductor distribution layer, an isolation groove is provided on the transparent conductive film layer corresponding to the boundary region between the N-type semiconductor region and the adjacent P-type semiconductor region, and an N-type region metal electrode and a P-type region metal electrode are provided on the outer surface of the corresponding transparent conductive film layer of the N-type semiconductor region and the P-type semiconductor region, the N-type semiconductor region and the P-type semiconductor region both comprising a silicon layer, the surface layer of the transparent conductive film layer is at least partially doped with a metal material to form a doped region, and the average doping concentration of the metal material in the doped region is 1e18cm -3 -5e22cm -3 The ratio of oxygen vacancies in the transparent conductive film layer to the total oxygen atoms contained is 5%-60%, and doping regions are respectively arranged on the transparent conductive film layers that the N-type region metal electrode and the P-type region metal electrode contact respectively. The silicon layer of the present invention can be, for example, amorphous silicon, microcrystalline silicon or polycrystalline silicon.
[0071] The proportion of oxygen vacancies in the transparent conductive film layer to the total amount of oxygen atoms contained is 5%-60%, and specific examples include 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc., and the range between any two point values.
[0072] Wherein, when the metal material is a metal of acceptor impurities in the silicon layer, the doping depth D1 of the doping region corresponding to the N-type semiconductor region is 20%-90% of the thickness of the transparent conductive film layer, and the doping depth D2 of the doping region corresponding to the P-type semiconductor region is 30%-100% of the thickness of the transparent conductive film layer; and D1 is less than D2. The D1 is less than D2, which means that under the same conditions, no matter the maximum value, minimum value or average value, D1 is less than D2, for example, the minimum value of D1 is less than the minimum value of D2, and the maximum value of D1 is less than the maximum value of D2.
[0073] Wherein, when the metal material is a metal of a donor impurity in the silicon layer, the doping depth D1 of the doping region corresponding to the N-type semiconductor region is 30%-100% of the thickness of the transparent conductive film layer, and the doping depth D2 of the doping region corresponding to the P-type semiconductor region is 20%-90% of the thickness of the transparent conductive film layer; and D1 is greater than D2. The D1 being greater than D2 means that under the same conditions, whether the maximum value, the minimum value or the average value satisfies D1 being greater than D2, for example, the minimum value of D1 is greater than the minimum value of D2, and the maximum value of D1 is greater than the maximum value of D2.
[0074] Preferably, when the metal material is a metal of an acceptor impurity in the silicon layer, the ratio of D1 to D2 is 1:1.25-6, preferably 1:1.4-5; when the metal material is a metal of a donor impurity in the silicon layer, the ratio of D1 to D2 is 1:0.3-0.8, preferably 1:0.3-0.5. This preferred solution is more conducive to avoiding the doping of metal elements with opposite polarity into the polycrystalline or amorphous layer to reduce the free carrier concentration.
[0075] In the present invention, the doping depth is measured by TEM, and is obtained by measuring the depth of the target element components at different positions of the section. Since the doping depth is affected by the heating level of the metal material, the size, distribution and relative position of the metal material will affect the microwave absorption, so the size of the metal material at different positions of the doping depth will be greatly different, so the doping depth is generally within a certain range.
[0076] The average value of the doping concentration of the metal material in the present invention refers to a simple arithmetic mean, that is, the average value of all values tested.
[0077] Through the above technical solution, the present invention enables the transparent conductive film layer to have different contact resistivities with the corresponding metal electrode and the corresponding semiconductor region, respectively, and can match different contact characteristics with corresponding semiconductors of different polarities, which is beneficial to improving the battery contact characteristics and enhancing the battery efficiency.
[0078] It can be understood that the portions of the transparent conductive film layer that are in contact with the N-type metal electrode and the P-type metal electrode are provided with doped regions, and other non-contact portions may be provided with doped regions as required.
[0079] In some preferred embodiments of the present invention, the metal material in the doped region is distributed in at least one of a dot-shaped, a line-shaped, and a mesh-shaped form. It is understood that the dot-shaped and the line-shaped can be, for example, Figure 3 and Figure 4 As shown. The linear or mesh distribution means that most (at least 60%) of the metal material in the doping region is distributed in a linear or mesh shape. Due to the characteristics of material preparation, it is inevitable that some of it is in a point shape.
[0080] Preferably, the doped metal material is a nano-metal material. The metal material is nano-scale, which is more conducive to improving the thermal efficiency of the metal material for microwave processing and avoiding the metal material being too large in size to produce significant microwave reflection and reduce the efficiency of microwave absorption.
[0081] In some preferred embodiments of the present invention, the metal material is selected from at least one of silver, zinc and tin.
[0082] Preferably, the metal as an acceptor impurity includes at least one of silver and zinc, and the metal as a donor impurity includes tin.
[0083] In some preferred embodiments of the present invention, the material of the transparent conductive film layer is an indium oxide-based film doped with at least one of tin, tungsten, titanium, zinc, and gallium, or a zinc oxide-based film doped with at least one of aluminum, gallium, and boron.
[0084] In some preferred embodiments of the present invention, when the metal material is a metal of acceptor impurities in the silicon layer, the ratio of the average value of the doping depth of the metal material in the partial doping region where the N-type region metal electrode and the P-type region metal electrode are in contact is 1:1.1-3, preferably 1:1.1-2; when the metal material is a metal of donor impurities in the silicon layer, the ratio of the average value of the doping depth of the metal material in the partial doping region where the N-type region metal electrode and the P-type region metal electrode are in contact is 1:0.5-0.9. This preferred solution is more conducive to matching the different contact requirements of the N-type semiconductor region and the P-type semiconductor region, and optimizing the contact characteristics of the semiconductor layers of the N-type semiconductor region and the P-type semiconductor region.
[0085] In the present invention, the average value of the doping depth refers to the average value of the sum of the maximum value and the minimum value of the doping depth.
[0086] The ratio of the average value of the doping depth of the metal material in the partial doping regions where the N-type region metal electrode and the P-type region metal electrode respectively contact each other is 1:1.1-3. For example, any point value among 1:1.1, 1:1.3, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.3, 1:2.5, 1:2.7, and 1:3, as well as the range between any two point values, can be used in the present invention.
[0087] The ratio of the average value of the doping depth of the metal material in the partially doped regions where the N-type region metal electrode and the P-type region metal electrode respectively contact each other is 1:0.5-0.9. Specifically, for example, it can be any point value among 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, and the range between any two point values, which can all be used in the present invention.
[0088] In some preferred embodiments of the present invention, on the plane where the back side is located, the area of the doped region accounts for 5%-80% of the area of the transparent conductive film layer, which is more conducive to controlling the local doping range, providing good contact characteristic optimization, and avoiding the situation where the NP region is short-circuited due to a large area or the contact characteristics are not significantly improved due to a small range.
[0089] On the plane where the back side is located, the area of the doped region accounts for 5%-80% of the area of the transparent conductive film layer. For example, it can be any point value among 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, and 80%, as well as the range between any two point values, which can be used in the present invention.
[0090] In some preferred embodiments of the present invention, the thickness of the transparent conductive film layer is 10-150nm. For example, any point value among 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, and 150nm, as well as the range between any two point values, can be used in the present invention.
[0091] The present invention adopts the transparent conductive film layer with the above-mentioned suitable doping area area ratio and / or suitable thickness ratio, which can effectively prevent metal ions from diffusing into the semiconductor layer corresponding to the bottom of the transparent conductive film layer, improve the contact characteristics of the semiconductor layer, and further help improve battery efficiency.
[0092] In some preferred embodiments of the present invention, the metal material is selected from silver.
[0093] Further preferably, the N-type region metal electrode and the P-type region metal electrode are both silver paste electrodes. The silver paste electrodes can be connected with the metal material silver, which is more conducive to improving the electrode contact characteristics and further improving the battery efficiency.
[0094] Preferably, in the present invention, the material of the metal material is at least partially the same as that of the corresponding metal electrode, which is more conducive to the hemispherical metal material on the surface of the transparent conductive film layer and the corresponding metal electrode to form good electrical contact after microwave treatment, thereby further reducing the overall contact resistivity of the battery.
[0095] In some preferred embodiments of the present invention, the semiconductor distribution layer also includes an overlapping region located between the N-type semiconductor region and the P-type semiconductor region, and the overlapping region is formed by extending the end of the P-type semiconductor in the P-type semiconductor region and overlapping the outer surface of the end of the adjacent N-type semiconductor region, and the isolation groove is opened on the transparent conductive film layer corresponding to the overlapping region.
[0096] Further preferably, a mask layer is provided between the overlapping P-type semiconductor and the N-type semiconductor in the overlapping region, or no mask layer is provided.
[0097] In some preferred embodiments of the present invention, the back side of the silicon wafer corresponding to the N-type semiconductor region is a polished surface, and the back side of the silicon wafer corresponding to the P-type semiconductor region is a textured surface.
[0098] In some preferred embodiments of the present invention, the back-contact cell with improved contact characteristics further comprises a front passivation layer and an anti-reflection layer disposed on the front side of the silicon wafer.
[0099] In a second aspect, the present invention provides a method for preparing a back contact battery, comprising the following steps:
[0100] S1. Providing a battery substrate, the battery substrate comprising a silicon wafer and a semiconductor distribution layer deposited on the back of the silicon wafer and comprising alternatingly arranged N-type semiconductor regions and P-type semiconductor regions; both the N-type semiconductor regions and the P-type semiconductor regions comprise a silicon layer;
[0101] S2, depositing a transparent conductive film layer on the back of the battery substrate, controlling the oxygen content of the coating atmosphere corresponding to the transparent conductive film layer to be 0.1%-3% by volume; and opening an isolation groove on the transparent conductive film layer corresponding to the boundary area between the N-type semiconductor region and the adjacent P-type semiconductor region;
[0102] S3, coating a nano-metal material on at least part of the outer surface of the transparent conductive film layer, wherein the coating distribution density of the nano-metal material on the area of the transparent conductive film layer corresponding to the N-type semiconductor region and the P-type semiconductor region is different and the coating distribution density is 2%-80% based on the projected area; the diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region and the P-type semiconductor region is at least partially different;
[0103] S4. Perform microwave heating treatment on the nano-metal material on the back side under the protection of inert gas, so that at least part of the nano-metal material is doped into the transparent conductive film layer to form a doping region, and the doping depth of the doping region is controlled to be 20%-100% of the thickness of the transparent conductive film layer, and the average doping concentration of the metal material in the doping region is 1e18cm -3 -5e22cm -3 ;
[0104] S5. Forming an N-type region metal electrode and a P-type region metal electrode on the outer surfaces of the corresponding transparent conductive film layers in the N-type semiconductor region and the P-type semiconductor region, respectively.
[0105] The battery substrate can be formed by the existing post-texturing preparation method, that is, after forming the N-type semiconductor layer, a second semiconductor opening area is opened, and then texturing cleaning is performed to form a texturing surface in the second semiconductor opening area and the front side, followed by depositing the P-type semiconductor layer, and then opening the first semiconductor opening area to expose the first semiconductor layer.
[0106] The preparation method of the transparent conductive film layer described in S2 can refer to the existing technology, as long as a transparent conductive film layer with a target oxygen doping amount and a target thickness is obtained.
[0107] The oxygen content of the coating atmosphere corresponding to the transparent conductive film layer is controlled to be 0.1%-3% by volume. For example, any point value among 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% and the range between any two point values can be used in the present invention.
[0108] In some preferred embodiments of the present invention, the nano-metal material in S3 is introduced in the form of nano-particles and / or nano-wires.
[0109] Preferably, the coated nanometal material is distributed in at least one of a dot-like, a line-like, and a mesh-like form. It is understood that when the nanometal material is introduced as nanoparticles, it is distributed in a dot-like form, and when the nanometal material is introduced as nanowires, it is distributed in a line-like and / or mesh-like form.
[0110] Preferably, the diameter of the nano metal material is 10-3000 nm, which is more conducive to improving the thermal efficiency of microwave absorption and reducing the absorption of microwaves due to surface reflection of microwaves by metal.
[0111] The diameters of the nanoparticles and nanowires are both within the range of 10-3000 nm. The present invention has no restriction on the ratio of nanoparticles and nanowires when the nanometal material comprises both nanoparticles and nanowires. Since nanoparticles are byproducts of the production of nanosilver wires, they can be used in the present invention.
[0112] Preferably, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region is 10-3000nm, preferably 50-3000nm, and the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region is 10-1500nm. The present invention uses nano-metal materials of different diameters for different N / P-type semiconductor regions. After microwave treatment, adjacent or overlapping nano-metal particles will melt and fuse to form larger spheres, forming different contact characteristics, which is more conducive to improving battery performance.
[0113] In the preferred embodiment of the present invention, when the metal material is a metal of acceptor impurities in the silicon layer, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region is 5-60 times, more preferably 6-60 times, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region is 1-40 times, more preferably 1.6-40 times the thickness of the transparent conductive film layer; when the metal material is a metal of donor impurities in the silicon layer, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region is 1-30 times, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region is 5-80 times the thickness of the transparent conductive film layer. The use of the transparent conductive film layer with a suitable thickness ratio of the present invention is conducive to the diffusion of metal ions in the transparent conductive film layer in the area where the nano-metal material is attached during microwave treatment, and the metal material with a suitable doping amount is obtained.
[0114] In the preferred embodiment of the present invention, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region is N1, and the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region is P1, and the following conditions are satisfied: when the metal material is a metal of an acceptor impurity in the silicon layer, N1 is greater than P1; when the metal material is a metal of a donor impurity in the silicon layer, N1 is less than P1. This solution can improve the microwave absorption efficiency of the nano-material in a specific region to a certain extent, and is conducive to the targeted adjustment of the impurity diffusion depth of the transparent conductive film layer in a specific semiconductor conductive region.
[0115] In the present invention, the diameters of the metal materials in different semiconductor conductive regions may be mixed with a small amount of extremely small or large particles due to the difference in size of most particles. A small amount of particles with abnormal sizes have a limited effect on the improvement of contact resistance. Therefore, to characterize the range of most particle sizes, the present invention uses the median of the statistical particle size for characterization, and limits the statistical range with a robust statistical method. The effective range is set according to the arithmetic mean of the particle diameter ±3 times the median absolute deviation (MAD). Particle sizes beyond the range are considered outliers and are not counted.
[0116] Further preferably, when the metal material is a metal of acceptor impurities in the silicon layer, the ratio of N1 to P1 is 1:0.01-0.9, preferably 1:0.1-0.9; when the metal material is a metal of donor impurities in the silicon layer, the ratio of N1 to P1 is 1:1.2-100, preferably 1:1.2-50. The adoption of this preferred solution is more conducive to the targeted fine adjustment of the diffusion depth of the nano-metal material in the N-type semiconductor region or the P-type semiconductor region during the microwave treatment process, avoiding excessive doping depth of opposite polarity and reducing the free carrier density of the amorphous or polycrystalline layer.
[0117] In the present invention, S3 may also be added with auxiliary agents such as dispersants or stabilizers, such as polyvinyl pyrrolidone (PVP), citric acid, etc., as long as they can be coated on a specific area by dispensing or inkjet printing, and can be selected according to actual needs.
[0118] In some preferred embodiments of the present invention, the coating area of the nano-metal material in S3 accounts for 5%-80% of the area of the transparent conductive film layer.
[0119] In some preferred embodiments of the present invention, the coating distribution density of the nanometal material in S3 on the transparent conductive film layer area corresponding to the preset N-type semiconductor region is 2%-30% by projected area, and the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset P-type semiconductor region is 15%-80% by projected area.
[0120] The present invention adopts nano-metal materials with suitable coating area and / or coating distribution density, and can obtain doping regions with suitable doping depth, which is more conducive to matching the optimization requirements of contact characteristics of N-type semiconductor regions and P-type semiconductor regions, and achieving better comprehensive optimization effects.
[0121] Further preferably, when the metal material is a metal of acceptor impurities in the silicon layer, the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset N-type semiconductor region is less than the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset P-type semiconductor region; when the metal material is a metal of donor impurities in the silicon layer, the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset N-type semiconductor region is greater than the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset P-type semiconductor region. This preferred solution is conducive to different doping of the transparent conductive film layer corresponding to the metal electrode areas of different polarities, and is more conducive to maximizing the improvement of the contact characteristics of the N-type semiconductor region and the P-type semiconductor region, thereby improving the battery efficiency. In the present invention, a suitable coating distribution density can be selected according to the required doping conditions, as long as the target doping degree is obtained.
[0122] In some preferred embodiments of the present invention, the microwave heating treatment in S4 lasts for 3-30 seconds. The microwave heating treatment lasts for a very short time and will not affect the semiconductor film layer under the transparent conductive film layer. It is more conducive to making the doped region of the nano-metal material away from the semiconductor film layer under the transparent conductive film layer while improving the electrode contact characteristics, thereby avoiding the possibility of adversely affecting the semiconductor film layer and affecting the battery efficiency.
[0123] The inert gas of the present invention may include at least one of nitrogen, helium and argon. Preferably, the inert gas of the present invention is nitrogen, which is stable and not easily ionized under microwave heating conditions, and is more conducive to effectively preventing oxidation during microwave heating.
[0124] In some preferred embodiments of the present invention, after the microwave heating treatment in S4, at least part of the nano-metal material is attached to the surface of the transparent conductive film layer in a hemispherical shape, and part of the hemispherical nano-metal material contacts the corresponding metal electrode material in S5, which is more conducive to improving the contact between the transparent conductive film layer and the metal electrode and reducing the contact resistance.
[0125] In some preferred embodiments of the present invention, the coating method of the nano-metal material in S3 is any one of inkjet printing, dispensing, and pad printing.
[0126] In some preferred embodiments of the present invention, when the metal material is a metal of an acceptor impurity in the silicon layer, the doping depth of the doping region corresponding to the N-type semiconductor region is controlled to be 20%-90% of the thickness of the transparent conductive film layer, and the doping depth of the doping region corresponding to the P-type semiconductor region is controlled to be 30%-100% of the thickness of the transparent conductive film layer;
[0127] When the metal material is a metal as a donor impurity in the silicon layer, the doping depth of the doping region corresponding to the N-type semiconductor region is controlled to be 30%-100% of the thickness of the transparent conductive film layer, and the doping depth of the doping region corresponding to the P-type semiconductor region is controlled to be 20%-90% of the thickness of the transparent conductive film layer.
[0128] In the present invention, the doping depth of the doping region can be adjusted by parameters such as the size of the nano-metal particles, the coating distribution density, etc. Under the same microwave conditions, the nano-metal particles with smaller diameters and appropriately increased coating distribution density have higher heat absorption efficiency and greater metal diffusion depth; the particles with larger diameters and more dispersed distribution have lower heat efficiency and smaller diffusion depth.
[0129] In the preferred embodiment of the present invention, when the metal material is a metal of acceptor impurities in the silicon layer, the specific method of controlling the different doping depths of silver ions in the two regions is that the diameter of the nanosilver particles set on the transparent conductive film layer in the N-type region is larger and the coating distribution density is smaller; when the same microwave energy is irradiated, the metal ion doping depth is less than the thickness of the transparent conductive film layer, and the preferred doping depth is 20%-80% of the thickness of the transparent conductive film layer, and the more preferred doping depth is 20%-50% of the thickness of the transparent conductive film layer; the diameter of the nanosilver particles set on the transparent conductive film layer in the P-type semiconductor region is small, the coating distribution density is large, the microwave absorption heat efficiency is slightly higher, and the metal ion doping depth is slightly greater than the depth in the transparent conductive film layer in the N-type region under the same microwave energy irradiation. When the metal material is a metal of donor impurities in the silicon layer, the above doping depth is just the opposite. Since tin metal is a donor impurity in polycrystalline and amorphous, it is necessary to control the doping depth on the P-type semiconductor region side.
[0130] In a third aspect, the present invention provides a back-contact battery with improved contact characteristics, which is prepared by the method for preparing a back-contact battery described in the second aspect.
[0131] In a fourth aspect, the present invention provides a photovoltaic module, which includes the back-contact cell with improved contact characteristics described in the first aspect, or includes the back-contact cell with improved contact characteristics described in the third aspect.
[0132] The embodiments of the present invention are described in detail below, which are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0133] Example 1
[0134] A back contact battery, such as Figure 1 As shown, it is prepared by the following preparation method:
[0135] S1. Provide a battery substrate, the battery substrate comprising a silicon wafer 1 and a semiconductor distribution layer deposited on the back of the silicon wafer 1 and comprising alternately arranged N-type semiconductor regions 21 and P-type semiconductor regions 22, the semiconductor distribution layer further comprising an overlapping region between the N-type semiconductor region 21 and the P-type semiconductor region 22 and a front passivation layer and an anti-reflection layer arranged on the front, the overlapping region being formed by extending the end of the P-type semiconductor of the P-type semiconductor region 22 and overlapping the outer surface of the end of the adjacent N-type semiconductor region 21; the back of the silicon wafer 1 corresponding to the N-type semiconductor region 21 is a polished surface, and the back of the silicon wafer 1 corresponding to the P-type semiconductor region 22 is a velvet surface;
[0136] S2, depositing a transparent conductive film layer (specifically ITO, with a thickness of 60nm on the plane and about 0.67 times the thickness on the textured surface, the same below) on the back of the battery substrate, controlling the oxygen content of the transparent conductive film coating atmosphere to be 0.6%, and the proportion of oxygen vacancies in the transparent conductive film layer to the total oxygen atoms contained is about 30%; and opening an isolation groove 33 on the transparent conductive film layer corresponding to the boundary area between the N-type semiconductor region 21 and the adjacent P-type semiconductor region 22;
[0137] S3. Coating nano-metal material 5 (specifically, a mixed material of nano-silver particles and nano-silver wires, with a diameter in the range of 10-1000 nm) on the outer surface of a portion of the transparent conductive film layer (including the first transparent conductive film layer 31 corresponding to the N-type semiconductor region 21 and the second transparent conductive film layer 32 corresponding to the P-type semiconductor region 22) by inkjet printing. The SEM images of the outer surfaces of the corresponding transparent conductive film layers of the N-type semiconductor region 21 and the P-type semiconductor region 22 are as follows: Figure 2 and Figure 5 As shown; the coating area accounts for 50% of the area of the transparent conductive film layer. The diameter of the nano-metal material 5 on the surface of the first transparent conductive film layer 31 corresponding to the N-type semiconductor region 21 is 50-1000nm, and the coating distribution density is 15% based on the projected area. The median diameter of the nano-metal material 5 in the doping region corresponding to the metal electrode in the N-type region (about 500nm) is 8.3 times the thickness of the transparent conductive film layer, and the median diameter of the nano-metal material 5 in the doping region corresponding to the metal electrode in the P-type region (about 80nm) is 2 times the thickness of the transparent conductive film layer. The diameter of the nano-metal material 5 on the surface of the second transparent conductive film layer 32 corresponding to the P-type semiconductor region 22 is 10-600nm, and the coating distribution density is 25% based on the projected area.
[0138] S4, the nano-metal material 5 on the back is subjected to microwave heating treatment under nitrogen protection for 13s, so that at least part of the nano-metal material 5 is doped into the first transparent conductive film layer 31 to form a first doping region 51, the doping depth of the first doping region 51 is 20%-70% of the thickness of the transparent conductive film layer, and the average doping concentration is 2e19cm -3 , at least part of the doping is doped into the second transparent conductive film layer 32 to form a second doping region 52, the doping depth of the second doping region 52 is 50%-100% of the thickness of the transparent conductive film layer, and the average doping concentration is 2e19cm -3 The ratio of the average doping depths of the first doping region 51 and the second doping region 52 is 1:1.7. The average doping depth refers to the average of the sum of the maximum and minimum doping depths. The SEM images of the outer surfaces of the N-type semiconductor region 21 and the P-type semiconductor region 22 respectively corresponding to the transparent conductive film layer after microwave heating treatment are as follows: Figure 4 and Figure 7 After microwave heating treatment, at least part of the nano-metal material 5 is attached to the surface of the transparent conductive film layer in a hemispherical shape, and part of the hemispherical nano-metal material 5 is in contact with the corresponding metal electrode material in S5.
[0139] S5. Print silver paste on the outer surfaces of the corresponding transparent conductive film layers of the N-type semiconductor region 21 and the P-type semiconductor region 22 to form the N-type region metal electrode 41 and the P-type region metal electrode 42 respectively.
[0140] In the obtained back contact battery, the N-type semiconductor region 21 and its upper and lower film layers are collectively referred to as the N-type region structure, and the P-type semiconductor region 22 and its upper and lower film layers are collectively referred to as the P-type region structure. The overall contact resistivity of the N-type region structure is 20.3 mΩ·cm tested by the linear transmission model TLM method. 2 The overall contact resistivity of the P-type region structure is 57.99 mΩ·cm 2 (The contact resistivity of the N-type region is tested using an N-type substrate, and the contact resistivity of the P-type region is tested using a P-type substrate, the same below).
[0141] Example 2
[0142] The method of Example 1 is followed, except that the coated nanosilver wires are replaced with an equal amount of nanosilver particles, that is, the coated metal material is all nanosilver particles. The SEM images of the outer surfaces of the corresponding transparent conductive film layers of the N-type semiconductor region and the P-type semiconductor region after microwave heating are as follows: Figure 3 and Figure 6 shown.
[0143] Correspondingly, the overall contact resistivity of the N-type region structure is 22.4 mΩ·cm 2 The overall contact resistance of the P-type region structure is 64.2mΩ·cm 2.
[0144] Example 3
[0145] The method of Example 1 is referred to, except that the coated nano-metal material is replaced by nano-tin particles as the metal material. The diameter of the nano-tin on the surface of the first transparent conductive film layer corresponding to the N-type semiconductor region is 10-200nm, and the coating distribution density is 25%; the diameter of the nano-tin on the surface of the second transparent conductive film layer corresponding to the P-type semiconductor region is 70-500nm, and the coating distribution density is 15%.
[0146] The nano-metal material on the back is subjected to microwave heating treatment under nitrogen protection for 5 seconds, so that at least part of the nano-metal material is doped into the transparent conductive film layer to form a first doping region 51, the depth of the first doping region 51 is 60%-100% of the thickness of the transparent conductive film layer, and at least part of the nano-metal material is doped into the transparent conductive film layer to form a second doping region 52, the depth of the second doping region 52 is 30%-80% of the thickness of the transparent conductive film layer. The average doping concentration of the metal material in the doping region is 5e19cm -3 The ratio of the average value of the doping depth of the metal material in the doped area where the N-type metal electrode and the P-type metal electrode contact each other is 1:0.7. The median diameter of the nano-metal material 5 in the doped area corresponding to the N-type metal electrode (about 100nm) is about 1.7 times the thickness of the transparent conductive film layer, and the median diameter of the nano-metal material 5 in the doped area corresponding to the P-type metal electrode (about 300nm) is about 7.5 times the thickness of the transparent conductive film layer.
[0147] Correspondingly, the overall contact resistivity of the N-type region structure is 23.7 mΩ·cm 2 The overall contact resistance of the P-type region structure is 95.3mΩ·cm 2 .
[0148] Example 4
[0149] The method of Example 3 is referred to, except that the coated nano-tin particles are replaced by a mixture of nano-tin wires and nano-tin particles.
[0150] Correspondingly, the overall contact resistivity of the N-type region structure is 22.5 mΩ·cm 2 The overall contact resistance of the P-type region structure is 71.8 mΩ·cm 2 .
[0151] Example 5
[0152] The method of Example 1 is referred to, except that the coating distribution density of the nano silver wires coated on the transparent conductive film layer corresponding to the N-type region metal electrode and the P-type region metal electrode is different, specifically: in S3, the coating distribution density of the nano metal material on the transparent conductive film layer area corresponding to the preset N-type region metal electrode is 5%, and the coating distribution density of the nano metal material on the transparent conductive film layer area corresponding to the preset P-type region metal electrode is 35%.
[0153] Correspondingly, the doping depth of the metal material in the partially doped area contacted by the metal electrode in the N-type region is 20%-50% of the thickness of the transparent conductive film layer, and the doping depth of the metal material in the partially doped area contacted by the metal electrode in the P-type region is 70%-100% of the thickness of the transparent conductive film layer.
[0154] The average doping concentration of the metal material in the doped area of the transparent conductive film layer corresponding to the N-type metal electrode is 1e19cm -3 The average doping concentration of the metal material in the doped area of the transparent conductive film layer corresponding to the metal electrode in the P-type region is 4e19cm -3 In this embodiment, due to the change in coating density of the N / P regions, the effective doping of the N-type semiconductor region will decrease, and the effective doping of the P region will increase, and the two regions will have different doping concentrations. The ratio of the average doping depth of the metal material in the doped regions where the N-type region metal electrode and the P-type region metal electrode are in contact is 1:2.4.
[0155] Correspondingly, the overall contact resistivity of the N-type region structure is 28.4 mΩ·cm 2 The overall contact resistance of the P-type region structure is 67.3mΩ·cm 2 .
[0156] Example 6
[0157] The method of Example 1 is referred to, except that the thickness of the transparent conductive film layer is adjusted: the thickness of the transparent conductive film layer on the plane (N-type region) is 100nm, the thickness corresponding to the textured surface (P-type region) is about 67nm, the proportion of oxygen vacancies to the total amount of oxygen atoms contained remains unchanged, and the microwave heating treatment time is increased to 18s. According to calculations, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region (about 500nm) is about 5 times the thickness of the transparent conductive film layer, and the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region (about 80nm) is about 1.2 times the thickness of the transparent conductive film layer.
[0158] Correspondingly, the doping depth of the metal material in the partially doped area contacted by the N-type region metal electrode is 20%-70% of the thickness of the transparent conductive film layer, and the doping depth of the metal material in the partially doped area contacted by the P-type region metal electrode is 50%-100% of the thickness of the transparent conductive film layer. The ratio of the average value of the doping depth of the metal material in the partially doped area contacted by the N-type region metal electrode and the P-type region metal electrode is 1:1.7.
[0159] Correspondingly, the overall contact resistivity of the N-type region structure is 25.7 mΩ·cm 2 The overall contact resistivity of the P-type region structure is 75.6 mΩ·cm 2 .
[0160] Example 7
[0161] The method of Example 1 is referred to, except that the nanosilver coating area is adjusted so that the area of the doped region on the back plane accounts for 10% of the area of the transparent conductive film layer.
[0162] Correspondingly, the overall contact resistivity of the N-type region structure is 26.2 mΩ·cm 2 The overall contact resistivity of the P-type region structure is 79.5 mΩ·cm 2 .
[0163] Comparative Example 1
[0164] The method of Example 1 is referred to, except that the transparent conductive film layer is not coated with nanosilver, that is, no doping region is formed. Accordingly, the overall contact resistivity of the N-type region structure is 39.1 mΩ·cm 2 The overall contact resistance of the P-type region structure is 106.4 mΩ·cm 2 .
[0165] Comparative Example 2
[0166] The method of Example 1 is carried out with reference to the method of Example 1, except that the microwave heating treatment is replaced by infrared lamp heating treatment, and a rapid thermal processing device is used, and the heat treatment temperature is 750°C for 1 min. The nanosilver of the transparent conductive film layer after heat treatment has a serious agglomeration phenomenon of nanoparticles in appearance, and the particle size increases significantly. Infrared heating is used to melt the nanosilver, but the heating of the silicon wafer also exists at the same time. The temperature of the battery substrate is not easy to control, and the passivation of the battery substrate is adversely affected. High temperature will cause heterojunction failure and poor battery efficiency.
[0167] Correspondingly, the overall contact resistivity of the N-type region structure is 22.6 mΩ·cm 2 The overall contact resistance of the P-type region structure is 62.7 mΩ·cm 2 .
[0168] Comparative Example 3
[0169] The method of Example 1 is referred to, except that the doping depths of the doping regions corresponding to the two semiconductor layers NP are adjusted to 100% of the thickness of the transparent conductive film layer. The process parameters that need to be adjusted to meet this condition are: the diameter of the nanosilver on the surface of the transparent conductive film layer corresponding to the N-type semiconductor region is 10-600nm and the coating distribution density is 60%; the diameter of the nanosilver on the surface of the transparent conductive film layer corresponding to the P-type semiconductor region is 10-600nm and the coating distribution density is 60%.
[0170] Correspondingly, the overall contact resistivity of the N-type region structure is 57.3 mΩ·cm 2 The overall contact resistance of the P-type region structure is 63.2 mΩ·cm 2 .
[0171] Comparative Example 4
[0172] The method of Example 1 is referred to, except that the doping depth of the doped region is adjusted to 20%-50% of the thickness of the transparent conductive film layer. The process parameters that need to be adjusted to meet this condition are: the diameter of the nanosilver on the surface of the transparent conductive film layer corresponding to the N-type semiconductor region is 60-1000nm and the coating distribution density is 10%; the diameter of the nanosilver on the surface of the transparent conductive film layer corresponding to the P-type semiconductor region is 60-1000nm and the coating distribution density is 10%.
[0173] Correspondingly, the overall contact resistivity of the N-type region structure is 30.4 mΩ·cm 2 The overall contact resistance of the P-type region structure is 74.7 mΩ·cm 2 .
[0174] Comparative Example 5
[0175] The method of Example 1 is referred to, except that the oxygen content of the coating atmosphere of the transparent conductive film layer is adjusted to 0%, that is, no oxygen is introduced during the preparation, and the oxygen vacancies in the transparent conductive film layer are not controlled. Accordingly, the overall contact resistivity of the N-type region structure is 93.8 mΩ·cm 2 The overall contact resistivity of the P-type region structure is 149.4 mΩ·cm 2 .
[0176] Test Case
[0177] The back contact cells obtained from the above embodiments and comparative examples were subjected to performance tests, wherein the NN contact resistivity refers to the overall contact resistivity of the N-type region structure electrode measured according to the linear transmission model TLM after the N-type substrate finished cell was cut; wherein the PP contact resistivity refers to the overall contact resistivity of the P-type region structure electrode measured according to the linear transmission model TLM after the P-type substrate finished cell was cut; the IV parameters of each example adopt the median value of each example grouping. The results are shown in Table 1. Among them, the unit of the corresponding contact resistivity is mΩ·cm 2 , the unit of short-circuit current Isc is A, the unit of open-circuit voltage Voc is V, the unit of fill factor FF is %, the unit of battery efficiency Eff is %, and the unit of series resistance Rs is Ω.
[0178] Table 1
[0179]
[0180] It can be seen from the above results that, compared with the comparative example, the embodiment scheme of the present invention can improve the contact characteristics between the metal electrode and the transparent conductive film layer, and the transparent conductive film layer and the semiconductor layer, enhance the conductivity of the transparent conductive film layer, and reduce the resistivity of the transparent conductive film layer. The overall resistance reduction effect is reflected from the macroscopic measurement, thereby improving the battery efficiency.
[0181] Further, according to Examples 1 and 2-7, it can be seen that the preferred battery structure of the present invention is more conducive to improving battery efficiency. Compared with Example 2 coated with all nanoparticles, Example 1 is a mixed particle, which can further reduce the transmission resistance of TCO under certain conditions, and the gain effect is better.
[0182] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A back contact battery with improved contact characteristics, comprising a silicon wafer, a semiconductor distribution layer comprising alternately arranged N-type semiconductor regions and P-type semiconductor regions disposed on the back of the silicon wafer, a transparent conductive film layer disposed on the outer surface of the semiconductor distribution layer, an isolation groove is provided on the transparent conductive film layer corresponding to the boundary region between the N-type semiconductor region and the adjacent P-type semiconductor region, and an N-type region metal electrode and a P-type region metal electrode are disposed on the outer surface of the corresponding transparent conductive film layer of the N-type semiconductor region and the P-type semiconductor region, wherein both the N-type semiconductor region and the P-type semiconductor region comprise a silicon layer, characterized in that: The surface layer of the transparent conductive film layer is at least partially doped with metal material to form a doped region, and the average doping concentration of the metal material in the doped region is 1e18cm -3 -5e22cm -3 The proportion of oxygen vacancies in the transparent conductive film layer to the total oxygen atoms contained is 5%-60%, and doping regions are respectively set on the transparent conductive film layers corresponding to the contact of the N-type region metal electrode and the P-type region metal electrode, wherein: When the metal material is a metal of an acceptor impurity in the silicon layer, the doping depth D1 of the doping region corresponding to the N-type semiconductor region is 20%-90% of the thickness of the transparent conductive film layer, and the doping depth D2 of the doping region corresponding to the P-type semiconductor region is 30%-100% of the thickness of the transparent conductive film layer; and D1 is less than D2; When the metal material is a metal as a donor impurity in the silicon layer, the doping depth D1 of the doping region corresponding to the N-type semiconductor region is 30%-100% of the thickness of the transparent conductive film layer, and the doping depth D2 of the doping region corresponding to the P-type semiconductor region is 20%-90% of the thickness of the transparent conductive film layer; and D1 is greater than D2.
2. The back contact battery with improved contact characteristics according to claim 1, characterized in that: When the metal material is a metal acceptor impurity in the silicon layer, the ratio of D1 to D2 is 1:1.25-6; When the metal material is a metal as a donor impurity in the silicon layer, the ratio of D1 to D2 is 1:0.3-0.
8.
3. The back contact battery with improved contact characteristics according to claim 1, characterized in that: The metal material in the doped region is distributed in at least one of a dot-shaped, a line-shaped, and a mesh-shaped form.
4. The back contact battery with improved contact characteristics according to claim 1, characterized in that: The doped metal material is a nano-metal material; and / or the metal material is selected from at least one of silver, zinc and tin.
5. The back contact battery with improved contact characteristics according to claim 1, characterized in that: The metal serving as an acceptor impurity includes at least one of silver and zinc, and the metal serving as a donor impurity includes tin.
6. The back contact cell with improved contact characteristics according to claim 1, characterized in that: When the metal material is a metal of acceptor impurities in the silicon layer, the ratio of the average value of the doping depth of the metal material in the doped regions where the N-type region metal electrode and the P-type region metal electrode contact each other is 1:1.1-3; When the metal material is a metal of a donor impurity in the silicon layer, the ratio of the average value of the doping depth of the metal material in the partially doped regions contacted by the N-type region metal electrode and the P-type region metal electrode is 1:0.5-0.
9.
7. The back contact battery with improved contact characteristics according to claim 1, characterized in that: On the plane where the back side is located, the area of the doped region accounts for 5%-80% of the area of the transparent conductive film layer.
8. The back contact battery with improved contact characteristics according to claim 1, characterized in that: The thickness of the transparent conductive film layer is 10-150nm.
9. The back contact battery with improved contact characteristics according to claim 1, characterized in that: The back contact battery with improved contact characteristics further includes at least one of the following structures: Structure 1: The semiconductor distribution layer also includes an overlapping region between the N-type semiconductor region and the P-type semiconductor region, the overlapping region is formed by extending the end of the P-type semiconductor of the P-type semiconductor region and overlapping the outer surface of the end of the adjacent N-type semiconductor region, and the isolation groove is opened on the transparent conductive film layer corresponding to the overlapping region; a mask layer is set between the overlapping P-type semiconductor and the N-type semiconductor in the overlapping region or no mask layer is set; Structure 2: The back side of the silicon wafer corresponding to the N-type semiconductor region is a polished surface, and the back side of the silicon wafer corresponding to the P-type semiconductor region is a velvet surface; Structure 3: The back contact cell with improved contact characteristics further comprises a front passivation layer and an anti-reflection layer arranged on the front side of the silicon wafer; Structure 4: The material of the metal material is at least partially the same as the material of the corresponding metal electrode; Structure 5: The metal material is selected from silver, and the N-type region metal electrode and the P-type region metal electrode are both silver paste electrodes.
10. A method for preparing a back contact battery, characterized in that: The steps include: S1. Providing a battery substrate, the battery substrate comprising a silicon wafer and a semiconductor distribution layer deposited on the back of the silicon wafer and comprising alternatingly arranged N-type semiconductor regions and P-type semiconductor regions; both the N-type semiconductor regions and the P-type semiconductor regions comprise a silicon layer; S2, depositing a transparent conductive film layer on the back of the battery substrate, controlling the oxygen content of the coating atmosphere corresponding to the transparent conductive film layer to be 0.1%-3% by volume; and opening an isolation groove on the transparent conductive film layer corresponding to the boundary area between the N-type semiconductor region and the adjacent P-type semiconductor region; S3, coating a nano-metal material on at least part of the outer surface of the transparent conductive film layer, wherein the coating distribution density of the nano-metal material on the area of the transparent conductive film layer corresponding to the N-type semiconductor region and the P-type semiconductor region is different and the coating distribution density is 2%-80% based on the projected area; the diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region and the P-type semiconductor region is at least partially different; S4. Perform microwave heating treatment on the nano-metal material on the back side under the protection of inert gas, so that at least part of the nano-metal material is doped into the transparent conductive film layer to form a doping region, and the doping depth of the doping region is controlled to be 20%-100% of the thickness of the transparent conductive film layer, and the average doping concentration of the metal material in the doping region is 1e18cm -3 -5e22cm -3 ; S5. Forming an N-type region metal electrode and a P-type region metal electrode on the outer surfaces of the corresponding transparent conductive film layers in the N-type semiconductor region and the P-type semiconductor region, respectively.
11. The method for preparing a back contact battery according to claim 10, characterized in that: In S3, the nano-metal material is introduced in the form of nano-particles and / or nano-wires, and the coated nano-metal material is distributed in at least one of the forms of dots, lines, and meshes, and the diameter of the nano-metal material is 10-3000nm.
12. The method for preparing a back contact battery according to claim 10 or 11, characterized in that: The median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region is 10-3000nm, and the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region is 10-1500nm; and / or, When the metal material is a metal of acceptor impurities in the silicon layer, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region is 5-60 times the thickness of the transparent conductive film layer, and the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region is 1-40 times the thickness of the transparent conductive film layer; when the metal material is a metal of donor impurities in the silicon layer, the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region is 1-30 times the thickness of the transparent conductive film layer, and the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region is 5-80 times the thickness of the transparent conductive film layer.
13. The method for preparing a back contact battery according to claim 12, characterized in that: The median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the N-type semiconductor region is N1, and the median diameter of the nano-metal material coated on the area of the transparent conductive film layer corresponding to the P-type semiconductor region is P1, and it satisfies: when the metal material is a metal of an acceptor impurity in the silicon layer, N1 is greater than P1; when the metal material is a metal of a donor impurity in the silicon layer, N1 is less than P1.
14. The method for preparing a back contact battery according to claim 13, characterized in that: When the metal material is a metal that is an acceptor impurity in the silicon layer, the ratio of N1 to P1 is 1:0.01-0.9; when the metal material is a metal that is a donor impurity in the silicon layer, the ratio of N1 to P1 is 1:1.2-100.
15. The method for preparing a back contact battery according to claim 10, characterized in that: The coating area of the nano-metal material in S3 accounts for 5%-80% of the area of the transparent conductive film layer.
16. The method for preparing a back contact battery according to claim 10 or 15, characterized in that: In S3, the coating distribution density of the nano-metal material on the transparent conductive film layer area corresponding to the preset N-type semiconductor area is 2%-30% by projected area, and the coating distribution density of the nano-metal material on the transparent conductive film layer area corresponding to the preset P-type semiconductor area is 15%-80% by projected area; And / or, when the metal material is a metal of acceptor impurities in the silicon layer, the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset N-type semiconductor region is less than the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset P-type semiconductor region; when the metal material is a metal of donor impurities in the silicon layer, the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset N-type semiconductor region is greater than the coating distribution density of the nanometal material on the transparent conductive film layer area corresponding to the preset P-type semiconductor region.
17. The method for preparing a back contact battery according to claim 10, characterized in that: The microwave heating treatment time in S4 is 3-30s.
18. The method for preparing a back contact battery according to claim 10, characterized in that: After the microwave heating treatment in S4, at least part of the nano-metal material is attached to the surface of the transparent conductive film layer in a hemispherical shape, and part of the hemispherical nano-metal material is in contact with the corresponding metal electrode material in S5; And / or, the coating method of the nano metal material in S3 is any one of inkjet printing, dispensing, and pad printing.
19. The method for preparing a back contact battery according to claim 10, characterized in that: When the metal material is a metal of acceptor impurities in the silicon layer, the doping depth of the doping region corresponding to the N-type semiconductor region is controlled to be 20%-90% of the thickness of the transparent conductive film layer, and the doping depth of the doping region corresponding to the P-type semiconductor region is controlled to be 30%-100% of the thickness of the transparent conductive film layer; When the metal material is a metal as a donor impurity in the silicon layer, the doping depth of the doping region corresponding to the N-type semiconductor region is controlled to be 30%-100% of the thickness of the transparent conductive film layer, and the doping depth of the doping region corresponding to the P-type semiconductor region is controlled to be 20%-90% of the thickness of the transparent conductive film layer.
20. A back contact battery with improved contact characteristics, characterized in that: The back contact battery is prepared by the method for preparing a back contact battery as claimed in any one of claims 10 to 19.
21. A photovoltaic module, characterized in that: It comprises the back contact cell with improved contact characteristics as claimed in any one of claims 1 to 9, or comprises the back contact cell with improved contact characteristics as claimed in claim 20.
Citation Information
Patent Citations
Transparent conducting assembly for crystalline silicon solar cell and preparation method thereof
CN105702757A
Method for preparing doped silicon wafer and solar cell
CN110137304A